Successful Oocyte Retrieval, Fertilization, and Clinical Pregnancy with Low Serum β-hCG on the Day of Oocyte Collection: A Reappraisal of the Definition of the Empty Follicle Syndrome - Nicole A. Van De Velde; Charalampos Chatzicharalampous; Awoniyi O. Awonuga (Case Reports in Obstetrics and Gynecology)
Objective. To describe a case of successful oocyte retrieval, fertilization and clinical pregnancy despite very low β-hCG level, twelve hours after ovulation trigger. Design. Case report. Setting. Academic medical center. Patient. A 38-year-old patient inadvertently administered 2,000 IU hCG for final oocyte maturation; serum hCG twelve hours later was 16 IU/L. Interventions. Effort to obtain and administer a booster dose of hCG over the next twenty-seven hours failed. Main Outcome. Successful oocyte retrieval. Results. Fourteen oocytes were retrieved of which twelve were in metaphase II and nine fertilized after intracytoplasmic sperm injection (ICSI). Of these, eight embryos survived to day 5 and were subjected to preimplantation genetic screening (PGS) by comparative genomic hybridization (CGH). Results were available the next day, three of the embryos were euploid and one was transferred on day 6. Pregnancy was confirmed twelve days later and currently the patient has an ongoing singleton intrauterine pregnancy. Conclusion. Reproductive Endocrinology and Infertility specialists should be aware that final oocyte maturation could occur following injection of a lower dose of hCG with excellent fertilization rate and embryo development.